2013
DOI: 10.15407/spqeo16.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of THz-electromagnetic wave transmission through the GaN films under conditions of cyclotron and optical phonon transit-time resonances

Abstract: Abstract. The theory of THz radiation transmission through the film of compensated GaN of cubic modification under action of electric and magnetic fields has been developed. In the THz frequency range, spectra of the dynamic mobility tensor have been obtained for applied steady-state electric fields of several kV/cm and magnetic fields of several T. The spectra of transmission, reflection and loss coefficients have been analyzed for the Voigt configuration used for the applied fields. It has been shown that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…The streaming regime and OPTTR can be identified in the optical experiments by the methods of THz-Fourier-or time-domain spectroscopies. The peculiarities of the THz transmission/absorption spectra for the GaN sample under conditions of OPTTR were analyzed in [21].…”
Section: Introductionmentioning
confidence: 99%
“…The streaming regime and OPTTR can be identified in the optical experiments by the methods of THz-Fourier-or time-domain spectroscopies. The peculiarities of the THz transmission/absorption spectra for the GaN sample under conditions of OPTTR were analyzed in [21].…”
Section: Introductionmentioning
confidence: 99%
“…The streaming regime and OPTTR can be identified in the optical experiments by the methods of THz-Fourier-or time-domain spectroscopies. The peculiarities of the THz transmission/absorption spectra for the GaN sample under conditions of the OPTTR were analyzed in [21].…”
Section: Introductionmentioning
confidence: 99%
“…We specified intervals of applied electric fields E (3…10 kV/cm), ambient temperatures T (30…150 K) and frequency ranges (0.2…2 THz), where streaming and OPTTR effects can occur [13,14]. Also, we investigated high-frequency properties of the compensated GaN under streaming conditions in the case of applied parallel magnetic field ( E H || ) [15,16] and found that this field has no effect on steady-state characteristics but essentially changes the frequency spectra of dynamic mobility tensor.…”
Section: Introductionmentioning
confidence: 99%